The many faces of narcissism: Narcissism factors and their predictive utility. (July 2015) - Clarke, Indako E.; Karlov, Lisa; Neale, Nicholas J.
Highlights: Exploratory factor analyses yielded eight factors from two narcissism measures. Narcissism factors reflected both adaptive and maladaptive content. Narcissism factors had differential relationships with psychological distress. 'Devaluing the Self' predicted depression, stress, and low self-esteem. 'Grandiose Exhibitionism' predicted high self-esteem. Abstract: Previous research has often portrayed narcissism as a unitary construct, however more recent research suggests it may be multidimensional. This study was conducted to examine the utility of two measures of narcissism – the Narcissistic Pathological Inventory and the Pathological Narcissism Inventory, in jointly assessing a broader range of narcissism content. The sample consisted of 220 undergraduate students. Eight factors were extracted from an exploratory analysis labeled: Contingent Self-Esteem, Grandiose Fantasy, Leadership/Authority, Devaluing the Self, Grandiose Exhibitionism, Manipulative, Entitlement, and Superiority. It was found that these narcissism factors had differing relationships with self-esteem, depression, anxiety, and stress. Although a higher-order factor structure did not have satisfactory fit, it is maintained that these eight factors reflect the two higher order dimensions of adaptive and maladaptive narcissism. It is recommended that future researchers construct their studies based on a multidimensional conceptualisation of narcissism, and use multiple narcissism measures.